Energy Absorption Study of Concrete Incorporating Spent Garnet Subjected to Low-Velocity Impact Loads - Khairuddin, Khairul Hafizie; Mokhatar, Shahrul Niza (Journal of Structural Monitoring and Built Environment, 2025)
Several researchers examine the concept of mitigating the impact during collisions between vehicles and concrete barriers, such as enhancing the energy absorption capacity of the barriers. As a result of this matter, this issue demands the use of sand, potentially resulting in the exploitation of natural resources. Hence, this study was utilizing waste material such as spent garnet (SG) as a partial fine aggregate replacement under low-velocity impact loads in order to predict the energy absorption produced from concrete containing SG. SG was used as a partial fine aggregate replacement using 0%, 10%, 20% and 30% of SG percentage. This study experimentally examines the compressive strength of sample which yielded at 43.5 MPa, 41.3 MPa, 42.1 MPa and 40.7 MPa for SG0, SG20, SG30 and SG40 respectively. The optimum percentage was chosen, and the block specimens were prepared for low-velocity impact test. All 12 block specimens were tested under a low-velocity impact test with fix velocity at 2.43 m/s. The results reveal that SG20 indicates ideal crater since the crater diameter almost same as diameter for nose hemispherical projectile used in this study which is 40 mm. The penetration depth for block specimens are 1.74 mm, 1.79 mm, 1.76 mm and 1.84 mm for SG0, SG20, SG30 and SG40 respectively. Thus, the results in penetration depth shows by the increment of SG content in the concrete mix produce higher penetration depth. In term of energy absorption, the result was directly proportional to penetration depth which the higher penetration depth produces higher energy absorption. Thus, the 20% SG mixture demonstrated the most promising result between compressive strength and energy absorption. This indicates that incorporating 20% SG into concrete barriers has significant potential for improving their performance, making them more effective in mitigating the impact of vehicle collisions and reducing the risk of fatalities.